Effect of the horizontal construction of carbon fibre plate insert to midsole on the elite runners` lower limb biomechanics - Fengqin, F.; Wang, J.; Qiu, C.; Li, S.; Ren, Q.; Yang, C.; Yang, F. (Footwear Science, 2025)
Introduction The construction of the Nike Vaporfly 4% shoe has led to the widespread incorporation of Advanced Footwear Technology (AFT) in modern running shoe design, characterised by the innovative use of a curved carbon fibre plate that significantly enhances propulsion and cuts down on energy costs (Frederick, Citation2022). Different carbon fibre-reinforced composite materials, like low curvature plates (LCP) and high curvature plates (HCP), adjust the ankle push-off moment by either increasing or decreasing it through changes in the lever arm (Farina et al., Citation2019). Despite the emphasis on longitudinal bending, the impact of horizontal scrolling on sports biomechanics, particularly considering the ubiquitous running motions such as foot eversion and calf internal rotation (Nigg et al., Citation2020), remains insufficiently researched, highlighting a key area for further investigation in the context of elite runner performance.